2013
DOI: 10.1111/myc.12086
|View full text |Cite
|
Sign up to set email alerts
|

Posaconazole prophylaxis – impact on incidence of invasive fungal disease and antifungal treatment in haematological patients

Abstract: Since two large-scale, randomised studies on posaconazole prophylaxis have demonstrated a clear benefit for patients at high risk for contracting invasive fungal disease (IFD), posaconazole prophylaxis has been adopted as standard of care for this patient collective. Several years on from implementation at our institution, we wanted to evaluate its impact on the incidence and use of empirical antifungal therapy in a real-life setting. We analysed retrospectively incidence and severity of IFD in high-risk patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
2
12
0
2
Order By: Relevance
“…Our observation of possible IFD in 21 % of patients correlates well with recently published data (Bourdelin et al 2014;Peterson et al 2013). The detection of aspergillus antigen by serum galactomannan assay was not implemented in our routine diagnostic procedure and might result in a lower frequency of possible IFD.…”
Section: Discussionsupporting
confidence: 91%
“…Our observation of possible IFD in 21 % of patients correlates well with recently published data (Bourdelin et al 2014;Peterson et al 2013). The detection of aspergillus antigen by serum galactomannan assay was not implemented in our routine diagnostic procedure and might result in a lower frequency of possible IFD.…”
Section: Discussionsupporting
confidence: 91%
“…In the last few years, some real‐life experiences confirmed the efficacy of posaconazole prophylaxis in this clinical setting, even if they were almost all retrospective studies and with historical comparisons (Table ) .…”
Section: From Bench To Bedsidementioning
confidence: 95%
“…For this reason, real-life studies may be of help in assessing whether results from randomized clinical trials can be translated into clinical practice. In the last few years, some real-life experiences confirmed the efficacy of posaconazole prophylaxis in this clinical setting, even if they were almost all retrospective studies and with historical comparisons (Table 2) [33,[57][58][59][60][61][62][63][64].…”
Section: From Bench To Bedsidementioning
confidence: 96%
See 1 more Smart Citation
“…However, factors such as epidemiologic features of the center, duration of neutropenia or response to the treatment for AML can influence the incidence of IFDs along with the type of the antifungal prophylaxis. Recently, a prospective observational study reported no difference in the incidence of IFDs in AML patients receiving remission-induction or consolidation therapy regarding to the type of AFP contrast to numerous studies in this field [6][7][8][9][10]. Also, a study from Turkey which included 50 patients with AML did not find any difference between posaconazole and fluconazole in terms of AFP failure [11].…”
Section: Introductionmentioning
confidence: 66%